2012
DOI: 10.1177/1759720x12437753
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline glucosamine sulfate in the management of knee osteoarthritis: efficacy, safety, and pharmacokinetic properties

Abstract: Abstract:Glucosamine is an amino monosaccharide and a natural constituent of glycosaminoglycans in articular cartilage. When administered exogenously, it is used for the treatment of osteoarthritis as a prescription drug or a dietary supplement. The latter use is mainly supported by its perception as a cartilage building block, but it actually exerts specific pharmacologic effects, mainly decreasing interleukin 1-induced gene expression by inhibiting the cytokine intracellular signaling cascade in general and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 70 publications
(138 reference statements)
5
32
0
15
Order By: Relevance
“…Показаниями для назначения являются первичный и вторичный остеоартроз, в том числе коленного, тазобе-дренного суставов, и спондилоартроз [6,8,14,25,27,29,32].…”
Section: рисунок 2 роль глюкозамина в синтезе гиалуроновой кислоты рunclassified
See 1 more Smart Citation
“…Показаниями для назначения являются первичный и вторичный остеоартроз, в том числе коленного, тазобе-дренного суставов, и спондилоартроз [6,8,14,25,27,29,32].…”
Section: рисунок 2 роль глюкозамина в синтезе гиалуроновой кислоты рunclassified
“…Противопоказаниями являются повышенная чувствитель-ность к препарату, наличие фенилкетонурии при приеме порошка внутрь, так как он содержит аспартам. Пациентам с тяжелыми нарушениями проводимости сердца, острой сердечной недостаточностью, при указании в анамнезе на эпилептиформные судороги, детям в возрасте до 12 лет, при беременности и в период лактации, а также при повышенной чувствительности к лидокаину противопо-казан раствор для внутривенного введения, так как он содержит лидокаин [11,26,29].…”
Section: рисунок 2 роль глюкозамина в синтезе гиалуроновой кислоты рunclassified
“…Crystalline glucosamine sulfate is a pharmaceutical-grade prescription product in Europe (but not in the United States or Canada) that consists of glucosamine, sulfate, sodium and chloride ions in a specific stoichiometric ratio (Altman, 2009). The other glucosamine salt forms (HCl, sulfate salts) have demonstrated variable efficacy in humans ( Sawitzke et al, 2010;Rovati et al, 2012). This is primarily due to inconsistency in glucosamine content amongst nutraceutical products and poor oral bioavailability, especially in combination with other nutraceutical additives (Altman, 2009;Sawitzke et al, 2010;Wandel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfate salt is often stabilized with sodium chloride (NaCl) or potassium chloride (KCl), which may be undesirable in aging canines with potential co-morbid medical conditions such as heart failure, hypertension or renal decline. Although this is a theoretical concern, human clinical trials have not demonstrated increases in blood pressure with NaCl content of crystallized glucosamine sulfate (Herrero-Beaumont et al, 2007;Rovati et al, 2012). Last, the hydrochloride salt is much cheaper to produce; keeping in mind that crystalline glucosamine sulfate is manufactured as pharmaceutical-grade with strict quality control standards (Altman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ряд исследований дока-зывает, что ХС достоверно влияет на клеточный компонент воспаления. Близким по фармакодинамике к ХС является ГС, который стимулирует хондроциты, повышает синтез протеогликанов, оказывая хондропротективное действие, а также подавляет выработку ИЛ-1, ИЛ-6, ФНОα, оказывая противовоспалительное действие [28][29][30][31]. Относительно недавно в научной литературе появился ряд исследова-ний по сочетанному применению ХС и ГС.…”
unclassified